Facebook as a Marketing Communication Media for Pempek UMKM products check chest Palembang - Joyo Pramudya; Isna Wijayani; Desy Misnawati; Siti Rahayu Pratami Lexianingrum (Dinasti International Journal of Education Management And Social Science, 2024)
The purpose of this research is to understand how Facebook can be used as a medium for promoting and marketing products of the small and medium enterprise (SME) Pempek Cek Dada Palembang. With the rapid development of the internet and technology, social media has become one of the best marketing tools for SMEs like Pempek Cek Dada to reach consumers more broadly and efficiently. As one of the largest social media platforms, Facebook has many features that can be used for marketing strategies. This research is conducted using qualitative methodology and a descriptive approach. Data is collected through in-depth interviews with the owner, employees, and customers of Pempek Cek Dada, as well as through observation and content analysis of their official Facebook page. The results of the study indicate that Facebook is effective as a communication and marketing medium for the products of Pempek Cek Dada. Features such as photo and video posts, and live streaming enable Pempek Cek Dada to convey product information in an engaging and interactive manner. Additionally, directly interacting with consumers through messages and comments on Facebook helps to increase consumer trust and build closer relationships.